Monkeypox – a cause of concern? - Umer Usman Malik; Muhammad Arham Bin Kashif; Ume Habiba (Journal of the Pakistan Medical Association, 2022)
Madam, the Monkeypox disease is a zoonotic infection caused by the Monkeypox virus of the Orthopoxvirus genus in the Poxviridae family. With a similar clinical presentation as the now eradicated smallpox, which includes fever, rash, and lymphadenopathy [1], the disease has remained endemic in Africa since the first reported case in the Democratic Republic of Congo in 1970. However, the latest news coverage has revealed new outbreaks of Monkeypox in non-endemic regions, which has left us wondering, ‘are we seeing the beginnings of a new Epidemic?’ Since its discovery, the number of reported cases of Monkeypox are on the rise, with the first case reported from outside Africa in 2003, when a Monkeypox outbreak reported from U.S.A following a shipment of Prairie dogs received from Ghana [2]. Between 2010-2019, cases were reported in the United Kingdom, Israel, and Singapore, all of which were associated with a recent travel history to Monkeypox endemic countries. As of 21 May 2022, the WHO reports 92 confirmed and 28 suspected cases of Monkeypox in humans from countries where the disease is non-endemic, with the highest numbers being reported in the UK, Spain, and Portugal. These cases are unique because the individuals involved were all infected locally, most of whom were men who had sex with men (MSMs) [3] , indicating a sexual mode of transmission that warrants further investigation. The cases being reported in the U.S.A and the U.K are concerning given the high number of international visitors to these countries, who may then spread the infection to their home countries. We believe that the emerging disease poses serious challenges within Pakistan and abroad. While new therapeutic agents (Tecovirimat) and a vaccine (MVA-BN) have been approved for Monkeypox, their availability remains limited. This issue would further be exacerbated by the challenges faced during the vaccination strategies used against Covid-19 in Pakistan [4]. Moreover, Human-to-human transmissions via sharing of beds and eating utensils has also been identified [5], which is concerning given Pakistan’s high population density and low socioeconomic status. We request that the respective Health authorities act to raise awareness of the disease. This may be accomplished by launching an Awareness Campaign using telecommunications and social media. Furthermore, screening of those with a recent travel history to countries with reported outbreaks should be conducted to curtail the spread of disease. –Continue